2018
DOI: 10.1017/s1047951117002864
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness and safety of anakinra in refractory Kawasaki disease complicated by coronary artery aneurysm

Abstract: Kawasaki disease is an acute self-limited vasculitis of unknown aetiology. The prognosis depends mainly on coronary damage. There is no consensus regarding optimal adjunctive therapeutics for refractory forms to treatment by intravenous immunoglobulins and corticosteroids. We report the case of an 18-month-old infant with refractory Kawasaki disease complicated by diffuse aneurysms of coronary arteries and successfully treated by anakinra with partial regression of coronary aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 11 publications
2
39
0
1
Order By: Relevance
“…Our findings demonstrate that Candida PAMPs initiate arteritis by activating TRMs in the aortic root and inducing chemokine and cytokine production in a mouse model of vasculitis resembling KD. Several case reports have shown promising results using the IL-1R antagonist Anakinra to treat KD (57,58) and new therapeutics that target the CCL2/CCR2 chemokine axis are currently in clinical trials for cancer (59,60). Finally, Syk inhibitors are available and have been in clinical trials for the treatment of rheumatoid arthritis (61).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrate that Candida PAMPs initiate arteritis by activating TRMs in the aortic root and inducing chemokine and cytokine production in a mouse model of vasculitis resembling KD. Several case reports have shown promising results using the IL-1R antagonist Anakinra to treat KD (57,58) and new therapeutics that target the CCL2/CCR2 chemokine axis are currently in clinical trials for cancer (59,60). Finally, Syk inhibitors are available and have been in clinical trials for the treatment of rheumatoid arthritis (61).…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, at least 5% of children remain febrile despite multiple dose of IVIG [18]. These particular patients are at even greater risk of CA complications, and additional therapies are usually administered [19], including corticosteroids [20][21][22], anti-TNF alpha agents [23,24], cyclosporine [25], cyclophosphamide [26] and more recently anakinra (anti-interleukine1) [27,28]. The use of these additional therapies is based on effectiveness in other vasculitis, with no prospective clinical trials to show effectiveness on coronary artery outcome.…”
Section: Discussionmentioning
confidence: 99%
“…e final case details response of a child with resistant KD who was then treated with anakinra around one month into disease with significant improvement of z-scores, although not complete normalization. Anakinra treatment in this case was 10 weeks [12]. In contrast to these cases, however a retrospective case series published in January 2018 analyzed multiple cases and found that anakinra showed "neither a striking nor a rapid decrease of coronary dilations" and could not determine if anakinra itself had effects on the CAA [13].…”
Section: Discussionmentioning
confidence: 68%